DATASET: Questionnaire results for university professors - Jiménez Perona, María Inmaculada; Fernández-Jiménez, Miguel Ángel; Leiva-Olivencia, Juan José (Universidad de Málaga, 2025)
Results from a sample of 223 university professors on knowledge, attitudes, and teaching uses regarding Generative Artificial Intelligence.
Keywords: Investigación activa en educación; Artificial intelligence; University professors; Higher education; Active research in education